Acidic retinoids synergize with vitamin A to enhance retinol uptake and STRA6, LRAT, and CYP26B1 expression in neonatal lung - Lili Wu; A. Catharine Ross (Journal of Lipid Research, 2010)
Vitamin A (VA) is essential for fetal lung development and postnatal lung maturation. VA is stored mainly as retinyl esters (REs), which may be mobilized for production of retinoic acid (RA). This study was designed 1) to evaluate several acidic retinoids for their potential to increase RE in the lungs of VA-supplemented neonatal rats, and 2) to determine the expression of retinoid homeostatic genes related to retinol uptake, esterification, and catabolism as possible mechanisms. When neonatal rats were treated with VA combined with any one of several acidic retinoids (RA, 9-cis-RA, or Am580, a stable analog of RA), lung RE increased ∼5–7 times more than after an equal amount of VA alone. Retinol uptake and esterification during the period of absorption correlated with increased expression of both STRA6 (retinol-binding protein receptor) and LRAT (retinol esterification), while a reduction in RE after 12 h in Am580-treated, VA-supplemented rats correlated with a strong and persistent increase in CYP26B1 (RA hydroxylase). We conclude that neonatal lung RE can be increased synergistically by VA combined with both natural and synthetic acidic retinoids, concomitant with induction of the dyad of STRA6 and LRAT. However, the pronounced and prolonged induction of CYP26B1 by Am580 may counteract lung RE accumulation after the absorption process is completed.